Profitability and Leverange on Firm Value in a Sharia Insurance Company - Destiana Kumala; Iyan Nurhasni Ahya (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
This study aims to examine the effect of profitability and leverage on firm value. The population in this study is a sharia insurance company listed on the Indonesia Stock Exchange (BEI). The independent variable of this study is a profitability (X1) which is measured using Return On Asset (ROA) and leverage (X) is measured the Debt Equity Ratio (DER), while the dependent variable of this study is the firm value (Y) as measured by Price Book Value (PBV). This research method uses quantitative research methods using purposive sampling method and based on predetermined criteria. From the sampling method used, there are 11 Islamic insurance companies listed on the Indonesia Stock Exchange (IDX) period 2016 – 2018. Data analysis techniques use regression analysis and path analysis using SPSS 22. The results show that profitability affects firm value and leverage, has no effect on firm value.